2019
DOI: 10.1097/md.0000000000017670
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of brain abscess in 183 patients

Abstract: This study aims to identify predictive factors related to clinical outcome, reoperation, and complications in patients with brain abscess. Patients with a diagnosis of brain abscess at discharge at the Second Affiliated Hospital of Zhejiang University School of Medicine between 2008 and 2018 were reviewed. Logistic regression was used to identify predictive factors associated with Glasgow Outcome Scale (GOS) at discharge, GOS at 1 year after discharge, reoperation and complications. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…e use of craniotomy for the treatment of abscess has significantly decreased while minimally invasive or image-guided aspiration techniques are now preferred as first surgical choice for abscesses. [32,42] Outcome in this study was unfavorable in 16% with a mortality rate of 9% [Table 2]. e deaths were due to delayed presentation, diagnosis, and intervention often attributable to poverty and ignorance.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…e use of craniotomy for the treatment of abscess has significantly decreased while minimally invasive or image-guided aspiration techniques are now preferred as first surgical choice for abscesses. [32,42] Outcome in this study was unfavorable in 16% with a mortality rate of 9% [Table 2]. e deaths were due to delayed presentation, diagnosis, and intervention often attributable to poverty and ignorance.…”
Section: Discussionmentioning
confidence: 86%
“…The use of craniotomy for the treatment of abscess has significantly decreased while minimally invasive or image-guided aspiration techniques are now preferred as first surgical choice for abscesses. [ 32 , 42 ]…”
Section: Discussionmentioning
confidence: 99%
“…Maximum abscess diameter was higher in patients who underwent a second procedure which may explain the recurrence of abscess formation in the rst place. Wu et al assured in their study that the surgical method plays a crucial role in predicting postsurgical complications and reoperation (6), they found that reoperation was more likely to be needed in patients who underwent aspiration, and that excision yields better clinical outcomes and more complications. In addition, due to the wide variety in the causative aetiological agents of brain abscesses, all patients need an empirical therapy and are recommended to undergo adjunctive systemic antibiotics management especially in cases of local and remote infections (1,7,17).…”
Section: Discussionmentioning
confidence: 99%
“…For centuries, brain abscesses had high morbidity and mortality rates which dramatically decreased with advances of culturing methods, neuroimaging, neurosurgical techniques, and antibiotic treatments, resulting in an earlier diagnosis, accurate localization and better management (3,4). However, it still threatens public health with an incidence of 0.4-0.9% worldwide, 1-2% in western countries and 8% of intracranial insults in developing countries (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…A cerebral abscess (CA) is an infection in the cerebral parenchyma that can arise as a complication of a variety of pathological conditions such as surgery, trauma, and as a result of other primary infections [1]. Most of the time, the clinical symptoms of brain abscess are related to intracranial hypertension (ICH), which is generally associated with secondary brain conditions in children, resulting in high morbidity and mortality, varying between 13% to 20% [2]. Brain abscesses are serious conditions, uncommon in the pediatric population, but of great clinical importance due to significant long-term mortality, demonstrating a prevalence of 0.4% to 0.9% for every 1000 people on a global scale [3].…”
Section: Introductionmentioning
confidence: 99%